Perception Analysis of Employees on Sharia Insurance at UPT. BP2MI - Atika Andriani; Tri Inda Fadhila Rahma (Management Department Universitas Islam Negeri Sumatera Utara, 2021)
Along with the development of Sharia insurance today, it is undeniable that many people, in general, do not know or do not understand it, which is considered new. Because so far, many people only know about conventional insurance because this type of insurance first appeared compared to Sharia insurance. The problem studied in this journal is the understanding of UPT employees. BP2MI against Sharia insurance. This research aims to find out how the perception of UPT employees. BP2MI against Sharia insurance. To reveal these issues in-depth and comprehensively, the researchers used qualitative methods that provided information and facts about the perceptions of UPT employees. BP2MI on Sharia insurance data is analyzed to answer these problems. From the results of this study, it was found that there are still many people who equate Sharia Insurance and Conventional Insurance, and there are still many people who do not know and become customers of Sharia Insurance. Due to the lack of socialization, promotion, and Sharia Insurance.Keywords: Perception, sharia insurance